2002
DOI: 10.3354/cr019193
|View full text |Cite
|
Sign up to set email alerts
|

Observed coherent changes in climatic extremes during the second half of the twentieth century

Abstract: A new global dataset of derived indicators has been compiled to clarify whether frequency and/or severity of climatic extremes changed during the second half of the 20th century. This period provides the best spatial coverage of homogenous daily series, which can be used for calculating the proportion of global land area exhibiting a significant change in extreme or severe weather. The authors chose 10 indicators of extreme climatic events, defined from a larger selection, that could be applied to a large vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

69
1,280
4
48

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,825 publications
(1,453 citation statements)
references
References 10 publications
69
1,280
4
48
Order By: Relevance
“…Daily temperature data were used to calculate length of growing season in any given year using the method described by Frich et al (2002).…”
Section: Methodsological Analysismentioning
confidence: 99%
“…Daily temperature data were used to calculate length of growing season in any given year using the method described by Frich et al (2002).…”
Section: Methodsological Analysismentioning
confidence: 99%
“…Frich et al (2002) found evidence of longer growing seasons and fewer frost days in much of the mid-and high latitudes in the Northern Hemisphere in the last 50 years. Furthermore, Heino et al (1999) found decreasing frost days across northern Europe during the twentieth century, and similarly, Bonsai et al (2001) also found decreasing frost days in Canada.…”
mentioning
confidence: 99%
“…Historical and future changes in the frequency, intensity, and duration of climate extremes have been increasingly studied in the last few decades using daily weather observation networks, global climate model (GCM) simulations [Frich et al, 2002;Alexander et al, 2006;Donat et al, 2013;Sillmann et al, 2013aSillmann et al, , 2013b, and regional climate model simulations [Iizumi et al, , 2012. At the global scale, GCM-projected climate extremes are translated into water scarcity, human health burden, food production loss, and degradation of ecosystem services using GCM output as the input of impact models (e.g., hydrologic and crop models).…”
Section: Introductionmentioning
confidence: 99%